GAYA KEPEMIMPINAN TRANSFORMASIONAL - Abdul Hakim; Amirulloh; Irnie Victorynie (STKIP Subang, 2025)
Leadership is an activity of influencing others so that they can work together to achieve the desired goals. One form of leadership is transformational leadership. Burns stated that the transformational leadership model essentially emphasizes that a leader needs to motivate his subordinates to carry out their responsibilities more than they expect. Transformational leaders must be able to define, communicate and articulate the vision of the organization, and subordinates must accept and acknowledge the credibility of their leaders. There are four dimensions included in it, namely idealized influence, Inspirational, Intellectual, Individualized consideration. Keywords: Leadership, Motivating, Organization;